Implementation of different technics for the monitoring of reinforced concretes corrosion applied to rebar embedded in concretes with ordinary and pozzolanic Portland cement - Vazquez, D.R.; Villagrán Zaccardi, Yury Andrés; Zega, Claudio Javier; Sosa, M. E.; Duffó, Gustavo Sergio (Elsevier, 2015)
Fil: Vazquez, D.R.. Comisión Nacional de Energía Atómica; Argentina. Universidad Nacional de San Martín. Instituto Sabato; Argentina